PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT DI KELAS V SDN 10 BANDAR BUAT - Hartati, Nia; Iraqi, Hana Shilfia (Jurnal Manajemen Pendidikan, 2026)
This study aims to improve students’ learning outcomes in Natural and Social Sciences (IPAS) through the application of the Teams Games Tournament (TGT) cooperative learning model. The research method used was Classroom Action Research (CAR), conducted in two cycles in the fifth-grade class at SDN 10 Bandar Buat. The results of the study indicate a significant improvement in all assessment aspects from Cycle I to Cycle II. The average score for the knowledge aspect increased from 71.96 (C) to 88.92 in Cycle II, earning a “good” (B) rating. In Cycle I, the average skill score was 80.64 (B), increasing in Cycle II to 89.87 with a “good” (B) rating. Based on these data, it can be concluded that the implementation of the TGT model successfully improved IPAS learning outcomes comprehensively, thus this study is deemed to have successfully achieved the established indicators.